How a non-allergist survives an allergy clinic. Issue 3 (20th February 2004) - Rosenthal, M
Abstract : This article is the result of six years of sudden, traumatic immersion therapy in the world of food allergy, following an innocent remark in 1996 from my then clinical director at Queen Mary's Children's Hospital, St Helier (Wrythe Lane, Surrey SM5 1AA), saying: "We really do not have much allergy service for children in this hospital. Why don't you start an allergy clinic?", and me, as a naïve relatively new consultant, agreeing. This has been added to by also doing the Paediatric Allergy Clinic at the Royal Brompton Hospital, with Professor Stephen Durham.